ANALISIS SIKLUS BISNIS DAN INDIKATOR EKONOMI PENDAHULU INDONESIA TAHUN 2000:Q2 â 2012:Q3 - , GALIH ADHIDHARMA; , Prof. Dr. Sri Adiningsih M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The economic growth of a country may experience fluctuations in forming business cycle caused by factors both within the country and abroad. The knowledge about the position of Indonesia's economy needs to be known mainly for the government, the monetary authority, and other economic actors including employers. By knowing the position and direction of the economy, the risks arising as a result of uncertainties can be minimized. This research will build a leading economic indicator which is a composite of macroeconomic indicators that comprise the financial sector, industry, and foreign trade which can predict macroeconomic conditions in Indonesia which was approached with the growth of Gross Domestic Product (GDP) using the growth cycles approach developed by the Organization for Economic Cooperation and Development (OECD). This study uses secondary data. GDP data as a reference series obtained from the Indonesiaâs National Bureau of Statistics (BPS). The indicators data series obtained from various sources such as BPS, Bank Indonesia, Indonesia Stock Exchange, and CEIC database. The frequencies of the data are quarterly. The observations period start from the second quarter of 2000 to the third quarter of 2012. Variables are Composite Stock Price Index, Car Sales, Number of Plane Passengers, Total Money Supply (M1), Cement Consumption, Export of Products Electrical Components and Export of Palm Oil. The method used in this study is the seasonally adjusted time series in the program Census X-12-ARIMA and band-pass filter of Christiano-Fitzgerald to get the business cycle of GDP and leading economic indicator series. The results of the leading economic indicators that successfully formed showed a high cross-correlation coefficient of 0.87.